Genetics in Sarcoidosis and Its Burden as a Multisystem Disease - Rivera, Natalia V.; Eklund, Anders (Seminars in Respiratory and Critical Care Medicine, 2025)
Sarcoidosis is a complex, immune-mediated disease characterized by a broad spectrum of clinical and molecular phenotypes—often referred to as endophenotypes—some of which progress to chronic outcomes such as pulmonary fibrosis. Despite decades of research, the pathogenesis of sarcoidosis remains incompletely understood, primarily due to its clinical heterogeneity and the absence of robust preclinical models. Established risk factors include age, sex, ethnicity, geographic origin, and environmental exposures, all of which contribute to granuloma formation and the activation of profibrotic pathways. These inflammatory cascades promote fibroblast proliferation and aberrant tissue remodeling, ultimately leading to interstitial lung pathology and fibrosis. A central feature of sarcoidosis is the dysregulation of immune regulatory mechanisms, likely driven by genetic susceptibility and immune dysfunction. Understanding the genetic architecture of sarcoidosis is crucial for identifying the molecular drivers of the disease, discovering biomarkers for early diagnosis and prognosis, and developing targeted therapies. This review synthesizes current knowledge on the genetic and genomic landscape of sarcoidosis, highlighting key loci and biological pathways implicated in disease susceptibility and progression.
Keywords: genetics; single-nucleotide polymorphisms; GWAS; human leukocyte antigen; MHC